2019
DOI: 10.1093/ee/nvz059
|View full text |Cite
|
Sign up to set email alerts
|

Coleoptera in the Canopy of the Cloud Forest From Tlanchinol in the State of Hidalgo, Mexico

Abstract: We describe the biodiversity, seasonal variation, and the possible edge effect of Coleoptera found in the canopy of the cloud forest in Tlanchinol in the state of Hidalgo. The coleopterans were collected by means of three fogging events during the dry season and another three during the rainy season in three sites of the forest: the edge, an intermediate, and an internal site. In total, 3,487 coleopterans were collected, belonging to 325 morphospecies from 52 families. The family with the largest number of mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
4
0
2
Order By: Relevance
“…[20] sampled 14.8% of the beetle species with at least 10 individuals, and Wagner [106] sampled 10.4% in Ugandan forest canopies. Fogging of the canopy of a cloud forest in Mexico revealed that only 17.3% of 325 morphospecies were collected with more than 10 individuals [96]. In the Pantanal of Brazil, 26.6% of the species were collected with at least 10 individuals on V. divergens [108] and 21.8% on the palm A. phalerata [127].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20] sampled 14.8% of the beetle species with at least 10 individuals, and Wagner [106] sampled 10.4% in Ugandan forest canopies. Fogging of the canopy of a cloud forest in Mexico revealed that only 17.3% of 325 morphospecies were collected with more than 10 individuals [96]. In the Pantanal of Brazil, 26.6% of the species were collected with at least 10 individuals on V. divergens [108] and 21.8% on the palm A. phalerata [127].…”
Section: Discussionmentioning
confidence: 99%
“…Although family systematics have been handled differently among studies, insecticide fogging methods often reveal more families associated with tropical rainforest trees. Davies et al [36], for instance, fogged 65 beetle families in a montane Neotropical rainforest, Márquez et al [96] fogged 52 families in a cloud forest in Mexico and Erwin and Scott [23] fogged 57 beetle families from a single tree species in Panama. Regardless of the sampling of 23 tree species during the night and day for a cumulative year, neither the species accumulation curves of single tree species assemblages nor for the entire assemblage attained any asymptote (figures 1 and 2).…”
Section: Sample Completenessmentioning
confidence: 99%
“…Además, estos tipos de vegetación se presentan primordialmente a altitudes por encima de los 1,500 m, y es donde encontramos un mayor porcentaje de riqueza de especies (76.8 %). Es importante señalar que existen áreas en el estado que han sido poco estudiadas para carábidos, pero en ellas se ha registrado una alta diversidad en otros grupos, por ejemplo, el municipio de Tlanchinol, donde se ha reportado un alto número de especies de Staphylinidae y Curculionidae (Márquez et al, 2019).…”
Section: Rango De Altitudunclassified
“…Las referencias de carábidos para el estado de Hidalgo son escasas, ya que la mayoría de los trabajos sobre coleópteros abordan otras familias. Algunos trabajos recientes han tenido un aporte limitado sobre carábidos, ya que su identificación se da a nivel de familia separando las distintas morfoespecies (Pedraza et al, 2010;Márquez et al, 2019). Sin embargo, se han realizado dos trabajos de tesis, uno sobre carábidos de la zona urbana y peri-urbana de Pachuca de Soto (Cerón-Gómez, 2016) y otro que abordó la taxonomía de Cicindelinae (como subfamilia de Carabidae; Ramírez-Hernández, 2018) de toda la entidad, con lo cual se aportaron registros precisos de especies para Hidalgo.…”
unclassified
“…51,000 species, with its higher species richness being recorded mainly in the tropics (Oberprieler et al 2014). Among ecological studies comprising Coleoptera diversity in tropical ecosystems, true weevils feature as one of the most diverse herbivorous (Iannuzzi et al 2003, Guedes et al 2019, Macedo-Reis et al 2019, Márquez et al 2019. True weevils feed on various plant organs, such as seeds, roots, leaves, and pollen, overcoming the structural and chemical defenses of plants (Anderson 1993, Oberprieler et al 2007.…”
Section: Introductionmentioning
confidence: 99%